HUBUNGAN ANTARA ADEKUASI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN DI UNIT HEMODIALISIS - Evi Ramayanti Purba; Derma Wani Damanik (Jurnal Keperawatan Priority, 2023)
Hemodialysis adequacy is an evaluation to measure hemodialysis effectiveness. Quality of life is a human perception of the life of cultural and value aspects where the individual lives in relation to goods, expectations, and standards. Haemodialysis is a therapy process by a renal substitute wearing a semi-permeable membrane that works as a nephron that can release metabolism residual and adjust fluid and electrolyte balance in patients with renal failure. This study aimed to determine the relationship between hemodialysis adequacy and quality of life in hemodialysis patients in the dialysis unit in Rumah Sakit Djasamen Saragih Pematangsiantar. This study used a cross-sectional design with 32 samples. The result shows that patients with inadequate dialysis were 28% (87,5%, and hemodialysis patients with poor quality of life 26 people (81,2%.) The analysis with the SPSS program obtained a statistical value of p <0,05, namely of 0,000 which means that there is a significant correlation between dialysis adequacy and quality of life of hemodialysis patients in Rumah Sakit dr. Djasamen Saragih Pematangsiantar. This result was used to improve the quality of health services and health counseling about dialysis adequacy in Rumah Sakit Umum Daerah dr. Djasamen Saragih Pematangsiantar to increase the patients’ knowledge about dialysis adequacy.